Perceptions of Physiotherapy students on aging - Santana, Pedro Paulo Corrêa (2020)
The present study aimed to analyze the perception of Physical Therapy students about aging. It was a qualitative research, carried out with 23 Physiotherapy students at a University Center in the city of Niterói, RJ, Brazil. A semi-structured interview was conducted, the content analysis technique was applied, according to Bardin. Data collection was carried out between the months of October and December 2019. The results reflect the importance of promoting the knowledge of Physiotherapy students in relation to aging in the training process, as it was evidenced that there are positive and negative aspects about practical aspects of aging and lack of knowledge about the propensity to imbalances, falls and injuries; the practice of exercises helping to improve cognitive functions and general clinical conditions; the elderly need not feel isolated or on the margins of society, but an important part in the construction. And it is concluded that there is a need to promote health based on the well-being aspects of the elderly, and contributing to the knowledge of Physiotherapy graduates, to ensure respectful and quality care when in their professional performance.